Gynecological Sarcomas: Molecular Characteristics, Behavior, and Histology-Driven Therapy. (February 2021) - Libertini, Michela; Hallin, Magnus; Thway, Khin; Noujaim, Jonathan; Benson, Charlotte; van der Graaf, Winette; Jones, Robin L.
Gynecological sarcomas represent 3% to 4% of all gynecological malignancies and 13% of all sarcomas. The uterus is the most frequent primary site (83%); less frequently sarcomas are diagnosed originating from the ovary (8%), vulva and vagina (5%), and other gynecologic organs (2%). As the classification of gynecologic sarcomas continues to diversify, so does the management. Accurate histopathologic diagnosis, utilizing appropriate ancillary immunohistochemical and molecular analysis, could lead to a more personalized approach. However, there are subtypes that require further definition, with regard to putative predictive markers and optimal management. The aim of this review is to highlight the importance of accurate diagnosis and classification of gynecologic sarcoma subtypes by the surgical pathologist in order to provide more tailored systemic treatment, and to highlight the increasing importance of close collaboration between the pathologist and the oncologist.